DEVELOPMENT DIRECTIONS AND PROBLEMS OF THE INSURANCE MARKET OF UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2023)
The insurance market of Uzbekistan has achieved significant growth in recent years under the influence of various factors such as economic reforms, increasing public awareness and favourable government policies. However, there are several problems that prevent the optimal development of the sector. This article aims to study the current situation of the insurance market of Uzbekistan, explore potential growth opportunities and solve important problems that require attention for the prosperity of the sector. Through this analysis, policymakers, industry stakeholders, and researchers can gain valuable insight into the necessary steps to ensure sustainable growth and remove barriers to Uzbekistan's insurance market.